BIOCHEMICAL GENETIC DIFFERENTIATION AMONG WILD POPULATIONS OF MILKFISH (Chanos chanos) IN INDONESIA - Ketut Sugama; Agus Prijono (Indonesian Fisheries Research Journal, 1998)
Four populations of milkfish (Chanos chanos ) were collected (N=100) from coastal water of  Aceh. Bali, East Java and South Sulawesi and were examined electrophoretically at 29 loci to deterurine the genetic vuriability and the population structure.